2012
DOI: 10.1371/journal.pone.0041261
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of TP53 Mutations in Benign and Malignant Salivary Gland Neoplasms

Abstract: Despite advances in the understanding of the pathogenesis of salivary gland neoplasms (SGN), the molecular pathways associated with enhanced tumor growth and cell survival remain to be established. The aim of the present study was to investigate whether TP53 mutations are relevant to SGN pathogenesis and if they impact on p53 protein expression. The study included 18 benign and 18 malignant SGN samples. Two polymorphic microsatellite markers at the TP53 genetic loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 34 publications
(33 reference statements)
1
15
1
1
Order By: Relevance
“…TP53 mutations have been previously reported in 25–33% of MEC, although only small numbers of MEC cases were included in those studies, which were not performed in an unbiased fashion(1820). Of the five tumors with TP53 mutations in our study, three were missense mutations and two were frameshift alterations.…”
Section: Discussionmentioning
confidence: 99%
“…TP53 mutations have been previously reported in 25–33% of MEC, although only small numbers of MEC cases were included in those studies, which were not performed in an unbiased fashion(1820). Of the five tumors with TP53 mutations in our study, three were missense mutations and two were frameshift alterations.…”
Section: Discussionmentioning
confidence: 99%
“…During the last 10 years, several molecular, genetic and immunohistochemical studies have been performed and consequently more knowledge obtained. Recent studies have indicated that PT53 mutations are not a frequent event in salivary gland tumours, benign as well as malignant [ 44 ]. Similarly, no amplifi cation/overexpression of HER2 is seen in PLGA [ 16 ].…”
Section: Histopathologymentioning
confidence: 99%
“…During tumorigenesis, somatic mutation of TP53 is one of the most common mechanisms of p53 inactivation. We have recently demonstrated that somatic mutations in the coding region of this gene are infrequent in salivary gland neoplasms . In addition to somatic mutation, TP53 function can also be modified/affected by genetic polymorphisms .…”
Section: Introductionmentioning
confidence: 99%
“…We have recently demonstrated that somatic mutations in the coding region of this gene are infrequent in salivary gland neoplasms. 4 In addition to somatic mutation, TP53 function can also be modified/affected by genetic polymorphisms. [5][6][7][8][9] There is an expanding body of literature suggesting that host factors, including genetic polymorphisms, may explain some of the variation in cancer occurrence among individual patients.…”
Section: Introductionmentioning
confidence: 99%